Catching fire - Collins, Suzanne (New York : Scholastic Press, 2009)
By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion.
Booklist starred
School Library Journal starred
Wilson's Senior High School
Booklist starred, July 2009
Bulletin (Center for Children's books), December 2009
Horn Book, April 2010
Keywords: Contests -- Juvenile fiction; Insurgency -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Contests -- Fiction; Insurgency -- Fiction; Interpersonal relations -- Fiction; Science fiction; Survival -- Fiction; Television programs -- Fiction; Contests -- Fiction; Insurgency -- Fiction; Interpersonal relations -- Fiction; Science fiction; Survival skills -- Fiction; Television programs -- Fiction; Science fiction